British vocational qualifications a directory of vocational qualifications available in the United Kingdom. (Kogan Page, 2008)
BVQ features up-to-date information on over 3,500 vocational qualifications available in the UK. It provides complete coverage of recent developments within the field, together with details of awarding, examining and validating bodies in one place.